DESAIN DAN UJI KINERJA GENERATOR AC FLUKS RADIAL MENGGUNAKAN 12 BUAH MAGNET PERMANEN TIPE NEODYMIUM (NdFeB) SEBAGAI PEMBANGKIT LISTRIK - Pramono, Gatot Eka; Muliawati, Fithri; Fajri Kurniawan, Nur (JUTEKS, 2017)
Technological developments encourage the use of electrical energy in large amounts which caused the crisis of it. One of solution to reduce the crisis is the utilization of renewable energy. The kind of renewable energy that is currently popular is like water energy, wind energy and ocean current energy which require low rpm generator devices without additional excitation. This research is to design an radial flux AC generator using the permanent magnet type neodymium (NdFeB) dimension of 50 mm × 15 mm × 6 mm, 12 units, with the number of stator coil windings 110 using copper wire diameter of 1 mm. The objective of this research was to obtain the results of the calculation of the strength of the shaft as well as the characteristics of the resulting voltage and power generator. An shaft of diameter 18 mm used in the planning calculations, otherwise in testing use the shaft of diameter of 20 mm. Actual shaft shear stress ? = 11.40 MPa, while the shaft shear stress permits ?a = 48.75 MPa. The calculation in the shaft produces: critical speed (Ncr) = 4462 rpm; The maximum deflection under the weight of the rotor, ymax = - 0.0477 mm; and deflection due to the rotation y = 0.617 mm. Tests without a load at 1075 rpm rotation obtained voltage of 101.4 V while the heater element 20 ? load was obtained a voltage of 64.7 V and a current was 2.40 A with calculation power result of 155.30 W.